Law on pharmacy - The National Assembly (2005)
This Law provides for drug trading; drug registration and circulation; drug use; drug supply; drug information and advertisement; clinical trial of drugs; management of habit-forming drugs, psychotrops, pre-substances used as drugs and radioactive drugs; drug quality standards and drug assay. Law applies to domestic and foreign agencies, organizations and individuals in Vietnam. Where international treaties to which the Socialist Republic of Vietnam is a contracting member contain provisions different from those of this Law, the provisions of such international treaties shall apply